(untitled) - Brock, Bert de (New York, 1995)
Providing a comprehensive theory of data modelling, this book explains the important concepts and principles with real-life examples showing how to apply it directly in practical applications. Topics covered include: a wide variety of functional requirements and query specification capabilities; a formal treatment of the semantics of the data; static and dynamic constraints and business rules; operations on tables, databases, and database universes; data dictionaries and their semantics; and comparisons of incidental properties and structural properties throughout the book. The book is aimed at professional database users such as designers, administrators and programmers, as well as specialists involved in data processing.
Keywords: Thiết kế cơ sở dữ liệu,Database design